Classification and characterization of endophytic actinomycetes isolated from cinnamomum cassia presl - Hanh Nguyen, Vu Thi; Son, Chu Ky; Tien, Phi Quyet (Vietnam Journal of Biotechnology, 2018)
Currently, antibiotic resistance in pathogenic bacteria is a significant clinical problem with the increase of deseases and a serious public health concern. Thus, the identification of new antimicrobial agents, especially the secondary metabolites products by endophytic actinobacteria from medical plants could be promising sources of biologically active compounds in medical fields. This study focused on identification and evaluation of antimicrobial activity against pathogens; genes involved in their secondary metabolisms, and screening of anthracycline producing capacity (mainly presented in anti-cancer antibiotics) of YBQ75 isolated from Cinnamomum cassia Presl. plants in Yen Bai province. Based on manual of bacterial classification, method in International Streptomyces Project (ISP) and the 16S rRNA gene sequence (GenBank Acc. No. KR814822), the endophytic actinomycetes YBQ75 was named Streptomyces cavourensis YBQ75 with 100% identity. The strain S. cavourensis YBQ75 showed the remarkable antibacterial activities against 5 tested pathogens (Salmonella enterica ATCC 14028 (22.0 mm); Pseudomonas aeruginosa CNLM (19.3 mm); Staphylococcus epidermidis ATCC 12228 (19.3 mm); Enterobacter aerogenes ATCC 13048 (17.7 mm) and Proteus vulgaris CNLM (16.3 mm)) in the total of 9 tested pathogens. The detection of genes involved in antibiotic synthesis indicated that the strain S. cavourensis YBQ75 consists of all three genes related to antibiotic synthesis including polyketide synthase (pks-I) type I, polyketide synthase type II (pks-II) and nonribosomal peptide synthetase (nrps). Premarilly result showed that the strain S. cavourensis YBQ75 also present as an anthracycline productive actinomycetes. The resutls demonstrated that the endophytic actinomycetes S. cavourensis YBQ75 from medical plants could be promising sources for the production of antibiotics and anthracycline anticancer compounds.